2014
DOI: 10.1016/j.neuroimage.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Fearful faces heighten the cortical representation of contextual threat

Abstract: Perception of facial expressions is typically investigated by presenting isolated face stimuli. In everyday life, however, faces are rarely seen without a surrounding visual context that affects perception and interpretation of the facial expression. Conversely, fearful faces may act as a cue, heightening the sensitivity of the visual system to effectively detect potential threat in the environment. In the present study, we used steady-state visually evoked potentials (ssVEPs) to examine the mutual effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 70 publications
5
57
0
Order By: Relevance
“…Conversely, participants who are on the lower end of the social anxiety continuum displayed a different and opposite pattern: face primes that indicated threat or ambiguity facilitated visual search. Results from low socially anxious participants are consistent with previous results with similar visual search tasks (Becker, 2009; Phelps, Ling & Carrasco, 2006; Wieser & Kiel, 2014; Quinlan & Johnson, 2011; Olatunji et al, 2011 Olatunji et al, 2015, Ferneyhough et al, 2013; Helfinstein et al, 2008). In all instances, for individuals who are higher on the anxiety continuum, priming with negative emotion stimuli decreased either attention bias or search efficiency.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Conversely, participants who are on the lower end of the social anxiety continuum displayed a different and opposite pattern: face primes that indicated threat or ambiguity facilitated visual search. Results from low socially anxious participants are consistent with previous results with similar visual search tasks (Becker, 2009; Phelps, Ling & Carrasco, 2006; Wieser & Kiel, 2014; Quinlan & Johnson, 2011; Olatunji et al, 2011 Olatunji et al, 2015, Ferneyhough et al, 2013; Helfinstein et al, 2008). In all instances, for individuals who are higher on the anxiety continuum, priming with negative emotion stimuli decreased either attention bias or search efficiency.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have demonstrated that early visual processes are affected by emotion primes, fearful primes in particular, and these effects are lasting. Neural evidence from steady state visual evoked potentials (ssVEP), thought to originate in early visual cortical regions, has demonstrated that a fearful cue facilitates identification of threat (Wieser & Keil, 2014). When a scene containing threat is preceded by a fearful face expression, ssVEP's to the threat scene increase, compared to other scenes (Wieser & Keil, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whalen et al, 2009, Wieser and Keil, 2014). Although other affective picture categories - such as mutilations - are also indirectly representing potential threat, we cannot provide inferences about a potential differential impact of threat predictability on direct threat.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, Wieser and Keil (2014) investigated the mutual effects of facial expressions (fearful, neutral, happy) and affective visual context (pleasant, neutral, threat) by assigning two different flicker frequencies (12 vs. 15 Hz) to the face and the visual context scene. While processing of the centrally presented faces was unaffected, viewing fearful facial expressions amplified the ssVEP in response to threatening compared to other background contexts.…”
Section: Ssvep Studies Of Socio-emotional Cue Perceptionmentioning
confidence: 99%